Amplifikasi Gen CRY1 dan Analisis Genom Isolat Bacillus thuringiensis Lokal - Dwi Suryanto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
A study on amplification of Cry1 gene and genome analysis of local isolate of Bacillus thuringiensis TU1 has been done. Amplification was done for cryI gene by PCR-technique. Genome analysis was performed using pulsed-field gel electrophoresis. Insecticidal specificity assay of the isolate to larvae was done in larvae of Heliothis armigera, Plutella xylostella, Aedes aegypti, and Culex sp. Isolate of commercial strain, B. thuringiensis var kurstaki strain HD-7, was used as control for amplification of cryI gene, genome analysis, and insecticidal specificity assay. The result showed that insecticidal specificity assay of the isolates of both TU1 and commercial have similar spectrum of toxicity to the larvae. Amplification of cry1 gene resulted to a fragment of approximately 550 bp in both TU1 and commercial. Genome profiles of TU1 and commercial strain were similar.